International experience and FDI location choices of Chinese firms: The moderating effects of home country government support and host country institutions - Lu, Jiangyong; Liu, Xiaohui; Wright, Mike; Filatotchev, Igor (Journal of International Business Studies, 2014)
We examine the extent to which Chinese government support of foreign direct investment (FDI) projects and host country institutional environments interact with prior entry experience by Chinese firms, and how this interrelationship affects FDI undertaken by Chinese firms. We hypothesize that home country government support and well-established host country institutions enhance organizational capabilities to take risks in FDI. As such, they reduce the need to accumulate experiential knowledge and capabilities relating to entering host countries based on prior entry experience in a particular country when undertaking follow-up investment projects. Using a unique, hand-collected panel data set of Chinese publicly listed firms during 2002–2009, we find that home government support and well-developed host country institutions reduce the importance of prior entry experience and significantly increase the likelihood of FDI entry into a host country. Further, from our subsample analyses we identify differences between entering developed and developing host countries in terms of the impact of home country government support and quality of host country institutions. Our findings help explain the puzzle concerning why emerging economy firms have rapidly internationalized in a short period of time and do not follow the pattern predicted by classical IB theories.